Disseminate Research in Science, Technology, Engineering and Mathematics (STEM) that Help in Creating Constructive Solutions in a Context of National and International Regulations - Samera Hussein Hamad (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2015)
Welcome to the open access, multi disciplines Journal of Civil Engineering and Environmental Sciences (JCEES).       We are delighted to announce that all the original work in the engineering, sciences and environment can be covered under the scope of JCEES. In the Civil Engineering and Environmental Science, we are bringing together the new ideas of different research activities from different fields (chemical, biological, andengineering related to environment and health) to encourage and advance the multidisciplinary research. It has been well known that there is a strong relations/interactions between the environmental compartments (air, water, and soil), and that understanding the chemical reactions and the biological interactions in all the environmental compartments provides insight in making decision on how to protect environment and human health. Therefore, we are putting together the real knowledge into the hands of everyone who are interested in understanding the chemical and the biological transformation of pollutants; this information together can be used to develop targeted solutions to pollution.